Fundamentals of bioorganic chemistry: textbook for medical studentsОсновы биоорганической химии: учебник для студентов учреждений высшего профессионального образования, обучающихся по специальностям 060101.65 "Лечебное дело", 060103.65 "Педиатрия", 060105.65 "Медико-профилактическое дело", 060201.65 "Стоматология" по дисциплине "Химия общая и биоорганическая" - Zurabyan, S. E. Sergey Eduardovich (GEOTAR-Media, 2015)
The textbook is based on modern organic chemistry and considers the structure and chemical transformations of organic compounds, especially those that have biological importance. Special attention is given to the chemical reactions that have analogies in living systems. The book contains about 250 problems on all topics and solutions for them. This book conforms to the Federal educational program on Bioorganic Chemistry for medical schools and universities. It is meant for students who study Bioorganic Chemistry during one term. The book may also be useful for teachers and students of specialized sec ondary schools with instruction conducted in English and colleges, whose main interest is medicine, pharmacy, biology and agriculture. Гриф Министерство образования и науки РФ. Рекомендовано ГОУ ВПО "Первый Московский государственный медицинский университет имени И.М. Сеченова" в качестве учебника для студентов учреждений высшего профессионального образования, обучающихся по специальностям 060101.65 "Лечебное дело", 060103.65 "Педиатрия", 060105.65 "Медико- профилактическое дело", 060201.65 "Стоматология" по дисциплине "Химия общая и биоорганическая"